Frequency of Anatomical Variations of Osteomeatal Complex among Patients with Chronic Rhinosinusitis - Soha Khan; Sadaf Khan; Aqsa Arif; Aneeqa Saleem (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of anatomical variations of osteomeatal complex in patients presenting with chronic rhinosinusitis. Study design: Descriptive cross-sectional study. Date and place of study: Department of Diagnostic Radiology, Combined Military Hospital, Multan, from Nov, 2024 to Apr, 2025. Methods: A total of 125 patients aged 18–65 years, clinically diagnosed with chronic rhinosinusitis (persistent symptoms lasting at least 12 weeks despite medication), and referred for CT scans of the paranasal sinuses were included in this study. A consultant radiologist identified anatomical variations of the osteomeatal complex. Descriptive statistics was applied to present the frequency and types of these variations. Results: The mean age of patients was 35.4 ± 11.2 years (range: 18–65 years). There were 59% males and 41% females. Anatomical variations of the osteomeatal complex were found in 112 (89.6%) patients. Most frequent variations were deviated nasal septum 82 (65.6%), concha bullosa 71 (56.8%), agger nasi cells 49 (39.2%), haller cells 34 (27.2%), pneumatized uncinate process 28 (22.4%), uncinate process deviation 25 (20%) and paradoxical middle turbinate 15 (12%). Conclusion: Anatomical variations of the osteomeatal complex are highly prevalent in patients diagnosed with chronic rhinosinusitis, with deviated nasal septum and concha bullosa being the most frequent variations observed in our population.